Implementasi Model Inquiry-Based Learning Dalam Pembelajaran Fisika Untuk Meningkatkan Keterampilan Berpikir Kritis - Merianti (CV. SINAR HOWUHOWU, 2025)
This research is motivated by the low critical thinking skills of students in Physics learning which is often conventional and teacher-centered. The purpose of this study is to describe the implementation of the Inquiry-Based Learning (IBL) model and its effectiveness in improving students' critical thinking skills. This study uses a qualitative approach with a case study design conducted on 32 grade XI MIPA students at a public high school in Medan. Data collection was carried out through observation, critical thinking skills tests (pre-test and post-test), interviews, and documentation. Data were analyzed qualitatively-descriptively to describe the learning process and quantitatively using paired sample t-tests and N-Gain to measure improvement. The results showed that the implementation of the IBL model ran well and succeeded in improving students' critical thinking skills significantly (p < 0.05). This is evidenced by an increase in the average score from 48.5 to 76.2, with an N-Gain value of 0.54 which is included in the